Host–Pathogen Interaction Involved in Trypanosoma cruzi Infection - Castillo, Christian; Kemmerling, Ulrike (MDPI, 2022)
Chagas disease, or American trypanosomiasis, caused by the protozoan parasite Trypanosoma cruzi (T. cruzi), is a silent, underdiagnosed, and life-threatening disease. Moreover, it constitutes a significant public health issue in Latin America and worldwide.
Keywords: Enfermedad de Chagas; Trypanosoma cruzi